Buenas Prácticas Ambientales y su contribución al desarrollo turístico en la Hostería Ñungañan cantón Pujilí. - Sánchez Aristega, Karen Elizabeth (2020)
The present Project is focused on the application of good environmental practices (GEP) in Ñungañan hostel, located in Recta de Vélez neighborhood, belonging to Pujilí canton, with the aim of improving the services that this business offers since there is a lack of awareness by part of the owners about this topic, a methodology of critical nodes was used which consist of identifying and prioritizing the problems by means of the application of strategies that will minimize the vulnerability of the tourist place regarding its services. With this in mind, the research has as the purpose to diagnose the contribution of the GEPs in the sustainable tourist development of the Ñungañan hostel. This study focuses on the descriptive research in which the criteria of the owners was taken, whose information was raised through ten non-structured interviews, which analyzed and interpreted with the goal of learning about the sustainable activities that they practiced. In agreement with the resulting principles of the business aspect, it can be detailed that the business does not have a manual that contains the policies of the hostel and the personal obligations. There is also a shortage of signaling of routes of evacuation to preserve the integrity of the visitor; regarding the environmental part, the restrooms should count with a system of water saving. That is why realizing a GEP manual is proposed, which will contribute to the betterment of the services of the hostel for a future certification. Therefore, the project has a positive environmental impact because practicing environmentally-friendly activities will achieve the preservation of natural resources.